RESERVES ESTIMATION OF A MARBLE QUARRY USING QUALITY INDICATORS - Kapageridis, I.; Albanopoulos, C. (Bulletin of the Geological Society of Greece, 2016)
The use of standard estimation and modelling software tools in estimating marble quarry reserves poses a number of challenges. Marble quarry reserves are based on marble quality categories, almost unique for each quarry/deposit considered. These categories represent visual and physical aspects of marble such as colour, texture and fractures. Classification of marble to one of the categories is performed by experienced personnel and is based on samples much smaller in area than the blocks of marble which are potentially exploited. The available information is, also, mostly qualitative leading to further complications in the application of geomathematical estimation methods. The estimation of marble reserves described in this paper is based on interpolating quality indicator values from drillhole and quarry face samples to blocks in three dimensions. The procedure is applied in all working quarries of Iktinos Hellas SA and is based on Maptek Vulcan Quarry Modeller, a mine planning package adapted for quarrying. Its application and results is demonstrated using a case study from one of the quarries in NE Greece.